Genome comparison of two Exiguobacterium strains from high altitude andean lakes with different arsenic resistance: identification and 3D modeling of the Acr3 efflux pump - Ordoñez, Omar F. (2015)
Fil: Fil: Ordoñez, Omar F. Planta Piloto de Procesos Industriales Microbiológicos (PROIMI). Laboratorio de Investigaciones Microbiológicas de Lagunas Andinas (CONICET); Argentina.